Complement C1q Binding Protein (C1QBP): Physiological Functions, Mutation-Associated Mitochondrial Cardiomyopathy and Current Disease Models - Wang, Jie; Huang, Christopher L-H; Zhang, Yanmin (Frontiers in Cardiovascular Medicine, 2022)
Complement C1q binding protein (C1QBP, p32) is primarily localized in mitochondrial matrix and associated with mitochondrial oxidative phosphorylative function. C1QBP deficiency presents as a mitochondrial disorder involving multiple organ systems. Recently, disease associated C1QBP mutations have been identified in patients with a combined oxidative phosphorylation deficiency taking an autosomal recessive inherited pattern. The clinical spectrum ranges from intrauterine growth restriction to childhood (cardio) myopathy and late-onset progressive external ophthalmoplegia. This review summarizes the physiological functions of C1QBP, its mutation-associated mitochondrial cardiomyopathy shown in the reported available patients and current experimental disease platforms modeling these conditions.